Model of Digital Marketing Communication of Sprite Rebranding - Daniel Susilo; Carl C.G. Dizon (CV. Media Digital Publikasi Indonesia, 2024)
Sprite is a widely recognised beverage brand renowned for its popular carbonated soft drinks worldwide. Among the various marketing models available, there exists a multitude of models that include diverse data. However, Sprite is demonstrating a distinct approach. While the consumption of soda is not widely prevalent in Indonesia, Sprite has implemented extensive promotional strategies to target and captivate the market, particularly the younger demographic. This study employed the Krippendorf Content Analysis approach to examine the Sprite Digital marketing Communication operations on Social media. According to the official Instagram account of the corporation in question, there appears to be a singular focus on promoting sustainability, with a particular emphasis on the efforts undertaken by the Sprite brand. Therefore, Sprite's commitment to a specific marketing strategy aimed at a significant objective demonstrates their capacity for sustainable development. The intricacy of Sprite's operational processes is once again demonstrated through the utilisation of digital content analysis